Design of Assessment and Evaluation of Islamic Religious Education (PAI) Learning - Latifatuz Zahra; Lathifah Lathifah; Abu Mansur; Baldi Anggara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
The aim of this research is to discuss the design of comprehensive assessment and evaluation for Islamic Religious Education (PAI) learning that is relevant to modern education. This research employed a qualitative approach with a library research approach, encompassing various scientific literature sources and Quranic interpretations. The results indicate that assessment and evaluation in PAI learning play a strategic role in measuring learning achievement while simultaneously shaping the religious character of students. However, practice in the field still tends to focus on the cognitive aspect through written tests, which does not reflect a holistic assessment. Therefore, it is necessary to design an assessment that covers the cognitive, affective, and psychomotor domains equally. Furthermore, PAI evaluation must be grounded in philosophical, psychological, and religious aspects that emphasize the harmony between knowledge and action. Assessment principles such as objectivity, fairness, comprehensiveness, and continuity are also important foundations for its implementation. The types of assessment used include diagnostic, formative, summative, and authentic assessments that complement each other. Thus, appropriate assessment and evaluation design can improve the quality of PAI learning and produce students who excel intellectually, spiritually, and socially.